Clinical and histopathological impact of biofilm in chronic rhinosinusitis with nasal polyps - Palanisamy, Karthikeyan; Vaid, Lakshmi; Gupta, Neelima; Saha, Rumpa; Singh, Usha Rani (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Presence of biofilms in sinus mucosa of patients with chronic rhinosinusitis (CRS) remains controversial. Literature shows that biofilms may contribute to the recalcitrant nature of CRS and unfavourable outcome following surgery. This study was performed to evaluate the prevalence of biofilm and its clinical and histopathological impact in patients with chronic rhinosinusitis with nasal polyps (CRSwNP) Methods: 41 patients of CRSwNP (study group) were included. SNOT-20(sinonasal outcome test-20) score, radiological and endoscopic findings of these patients were evaluated preoperatively. Sinonasal polypoidal tissues removed during surgery were studied for the presence of biofilm and evaluated histopathologically. Postoperatively SNOT-20 score and endoscopic finding were recorded. 41 patients undergoing septoplasty for deviated nasal septum (control group) were also included in the study. Sinonasal mucosal samples of these patients were analysed for the presence of biofilm. Results: 29 out of 41 (70.73%) samples in study group and 9 out of 41 (21.9%) samples in control group were positive for biofilm. We found a significant impact in preoperative SNOT-20 symptom scores in biofilm positive study group. But there is no significant impact in preoprerative endoscopic scores, radiological scores and postoperative SNOT-20 scores and endoscopic scores in study group patients irrespective of biofilm status. Conclusions: Prevalence of biofilm in patients with CRSwNP was higher than normal population. Biofilms plays a major role in preoperative symptomatology. But biofilms have no endoscopic, radiological, and histopathological impact in CRSwNP. It was concluded that apart from biofilms, host and other environmental factors plays a major role in the pathogenesis of CRSwNP.